Effect of Long Coriander Leaf (Eryngium Foetidum) Extract as a Natural Antioxidant on Chicken Meatballs During at Freezing Temperature - Boby, F; Hossain, MA; Hossain, MM; Rahman, MM; Azad, MAK; Hashem, MA (SAARC Journal of Agriculture, 2022)
The study was envisaged to evaluate the effect of different levels of long coriander (Eryngium foetidum L.) leaf extract on the quality attributes of chicken meatballs. The chicken meat sample was collected from local market of Mymensingh. The sample was quickly shifted to “Animal Science Laboratory” and carried out for laboratory analyses after refrigerated at -20ºC up to 90 days. Chicken meatball samples were divided into four treatment groups viz. control group (T0), 0.01% beta hydroxyl toluene (BHT) (T1), 0.5% long coriander leaves extract (T2), and 1% long coriander leaves extract (T3). Days of intervals were 0, 30 and 90 days. An ANOVA of a 4×3 factorial experiment in completely randomized design having three replications per treatment was used for data analyses. Sensory, proximate, physicochemical, biochemical and microbiological analyses were determined. Color, flavor, Juiciness, tenderness and overall acceptability increased significantly (p<0.05) in T2 and T3 treatments but decreased at different days of intervals. Dry matter (DM), crude protein (CP), ether extract (EE) and ash content decreased significantly (p<0.05) in T2 and T3 treatments and increased with days of intervals. Raw pH and cooking loss were decreased significantly (p<0.05) in T2 and T3 treatments and decreased with increased days of intervals. Free fatty acid (FFA), peroxide value (POV) were decreased significantly (p<0.05) in T2 and T3 treatments and increased with days of intervals. Thiobarbituric acid reactive substances (TBARS) were significantly (p<0.05) constant in T0, T2 and T3 treatments. Total viable count (TVC), total coliform count (TCC) and total yeast-mold count (TYMC) decreased significantly (p<0.05) in T2 and T3 treatments. Hence, sensory, physicochemical, biochemical and microbial properties indicate that 1% long coriander leaves extract was the best among all treatment groups. So, 1% long coriander leaves extract may be recommended for chicken meatballs as enriched natural antioxidant. SAARC J. Agric., 19(2): 271-283 (2021)